ENHANCING STUDENTS’ COMMUNICATIVE COMPETENCE THROUGH RUSSIAN LANGUAGE INSTRUCTION IN UZBEKISTAN’S PEDAGOGICAL UNIVERSITIES - Usarov Ravshan Khudayarovich; Ponomareva Lyudmila Ivanovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
The article examines the need to introduce innovative communication technologies into the pedagogical process of higher education institutions in the Republic of Uzbekistan. On the one hand, this necessity is supported through normative and legal documents; on the other, it demonstrates the importance of developing communicative competence in students for solving future professional tasks—specifically, teaching Russian in Uzbekistan’s schools. The authors emphasize that ongoing socio-economic changes in modern society impose on professional education the responsibility to form essential professional competencies in university graduates. Among these, communicative competence plays a crucial role in the personal and professional profile of future teachers, ensuring productive interaction among all participants in the educational process. The use of non-standard forms of instruction—particularly the integration of academic disciplines aimed at improving students’ communicative competence on independent and creative bases—is grounded in active interaction between subjects of the educational process.